Aplicabilidade da hipótese das seções planas a peças com variação linear ou parabólica da altura da seção transversal - Mansur, Webe João (1975)
The purpose of this work is to verify the correctness of the limitations established in Chapter 2, Item A.9, of the Brazilian Standard Code NB-1 according to which the inclination of haunchs used to settle the height of slabs and beams at the supports must be 1/3 as a maximum. This study embodies a comparation of the behavior of a symmetric fixed-end beam with retangular cross section analysed by the finite element method and by the theory of mechanics of materials, adopting in the last analysis two hypotheses relative to the axis of the beam: 1. The axis is straight; 2. The axis is the line passing through the midheight of the cross section. The analysis of the beam, according to the second hypothesis, leads to better results than the first one. The limitation imposed by NB-1 Standard Code (inclination of haunchs smaller than 1/3) is correct. There is a computer program herein, for the analysis of plane frames with haunched members.